The Role of Media Communication in Effective Communication for the Continuity of Business Negotiation Processes - Damara Febdwi Anandi (Telaah Bisnis, 2023)
This research discusses the crucial role of media communication in ensuring effective communication for the continuity of business negotiation processes. Utilizing a qualitative research method, the study delves into factors influencing effective communication, the concept of effective communication in negotiations, and methods for determining effective communication media. The analysis incorporates the implications of media richness theory, emphasizing the need for negotiators to thoughtfully consider the complexity of negotiation issues when selecting communication channels. The study also addresses limitations acknowledged in the literature, particularly challenges associated with the dynamic nature of technology and cultural diversity. By synthesizing insights from qualitative research and literature review, this study offers comprehensive guidance for negotiators and practitioners, facilitating a deeper understanding of the intricate dynamics surrounding effective communication and media selection in the context of business negotiations.The objective is to understand the importance of communication media and the types of communication media used by negotiators in both small and large-scale business negotiation activities. In this research, a qualitative approach is employed, characterized by data that is presented in its natural context and as it is.